In-situ characterization of radiation hardness of scintillating targets using heavy ion beams - Saifulin Maxim; Boutachkov Plamen; Kindler Birgit; Lommel Bettina; Walasek-Höhne Beata (EPJ Web of Conferences, 2025)
Scintillating materials are of interest for numerous applications related to ionizing radiation. Exposure to radiation induces damage in these materials, resulting in degradation of their scintillation properties. The knowledge of radiation damage rate as a function of dose is especially important when scintillators are exposed to heavy-ion beams. In this contribution, we report the development of a setup for in-situ characterization of radiation damage of scintillation targets exposed to heavy-ion beams. This setup provides a unique opportunity to study scintillating properties of materials under heavy ion exposure with energies of 300 MeV/u and above. The description of the setup and the sample characterization procedure are discussed on the basis of a study of zinc oxide ceramic scintillators.